PARAMETERS OF HEALTH CARE SYSTEMS - V. V. Omelyanovskiy; I. V. Maksimova; A. P. Tatarinov (Фармакоэкономика, 2015)
selection of the best model of health care to ensure more efficient use of resources to improve the quality and accessibility of health careis essentialin any country. The Russian Federation is not an exception. Currently the country has a mixed budgetary-insurance health care model, the transition to which startsin 1991, when the Law #1499-I "On Medical Insurance of the citizens of the Russian Federation"was approved.With the introduction of the Law "On Compulsory Medical Insurance in the Russian Federation"#326-FZ of November 29, 2010 the course was taken to develop the insurance model of health care system, however it had still not been implemented, and the insurance principle is not earned.